Filtração do ar: análise de dados da poluição ambiental e controle da poluição do ar por membranas de r-PET com CuNP - Machry, Karine (2024)
The growing concern about the risks to human health due to increasing pollution makes the use of efficient filters in ventilation systems essential for maintaining indoor air quality. Thus, the general objective of this work was to propose solutions to the problem of aerosol and bioaerosol pollution. Specific objectives included developing a literature review of particulate matter (PM) pollution with a diameter less than 10 µm, developing a model to predict PM concentration, and producing a filtering medium using the electrospinning technique with bactericidal and antiviral effects. In the context of air quality forecasting, a M P10 prediction model was developed for the region of São Carlos and Araraquara municipalities using data from 2014 to 2022. An XGBoost model was used to generate air quality forecast data, enabling the estimation of M P10 concentration up to 28 days in advance in the region using temporal variables. During the months of July to October, PM concentration in the environment can reach the highest values of the year, making it crucial to increase precautions during this period. In the development of the filtering medium, Recycled Polyethylene Terephthalate (r-PET) was used as the precursor polymer dissolved in a solution (30/70 w/w) of trifluoroacetic acid (TFA) and dichloromethane (DCM). Copper Nanoparticles (CuNP) were added to the filtering medium to confer antimicrobial and antiviral activity, obtained through a redox reaction. The r-PET nanofibers were characterized for morphology by SEM coupled with an EDS system for chemical mapping. The air-filtering medium obtained in this work was characterized for air filtration efficiency and permeability, showing high efficiency (95%) for filtering particulate matter (NaCl) below 90 nm. CuNP-impregnated nanofibers were able to reduce gram-positive and gram- negative bacteria growth by 99.99% after 3 hours of contact with the nanofibers. For viruses, this reduction was 99.13%, indicating that CuNP-coated nanofibers have both antiviral and antibacterial effects. The membranes obtained in this work can be used in air filtration, such as in portable air filters for purifying environments, due to their permeability, pressure drop, efficiency, and bactericidal and virucidal effects. Filters with high efficiency and biocidal effects can ensure user safety in combating diseases and infections by pathogenic microorganisms, as well as in preventing risks related to environmental pollution.